Decreased xanthine oxidoreductase is a predictor of poor prognosis in early-stage gastric cancer. Issue 9 (25th August 2006) - Linder, N; Haglund, C; Lundin, M; Nordling, S; Ristimäki, A; Kokkola, A; Mrena, J; Wiksten, J-P; Lundin, J
Abstract : Background: Xanthine oxidoreductase (XOR) is a key enzyme in the degradation of DNA, RNA and high-energy phosphates. About half of the patients with breast cancer have a decrease in XOR expression. Patients with breast cancer with unfavourable prognosis are independently identified by the loss of XOR. Aim: To assess the clinical relevance of XOR expression in gastric cancer. Methods: XOR levels were studied by immunohistochemistry in tissue microarray specimens of 337 patients with gastric cancer and the relation between XOR expression and a series of clinicopathological variables, as well as disease-specific survival, was assessed. Results: XOR was moderately decreased in 41% and was undetectable in another 14% of the tumours compared with the corresponding normal tissue. Decreased XOR was associated with advanced stage, deep tumour penetration, diffusely spread tumour location, positive lymph node status, large tumour size, non-curative disease, cellular aneuploidy, high S-phase fraction and high cyclooxygenase-2 expression, but not with p53 expression or Borrmann classification. Down regulation of XOR was associated with unfavourable outcome, and the cumulative 5-year gastric cancer-specific survival in patients with strong XOR expression was 47%, compared with 22% in those with moderate to negative expression (p<0.001). This was also true in patients with stage I–II (p = 0.01) and lymph node-negative (p = 0.02) disease, as well as in patients with smaller (⩽5 cm) tumours (p = 0.02). Conclusion: XOR expression in gastric cancer may be a new marker for a more aggressive gastric cancer biology, similar to that previously reported for breast cancer.